IMPLEMENTASI PENDIDIKAN KARAKTER TANGGUNG JAWAB DAN KERJA SAMA DI DALAM PEMBELAJARAN TEMATIK KURIKULUM 2013 DI SD NEGERI 2 BERKOH - Rifa Pramasanti; Dhi Bramasta; Subuh Anggoro (Teacher Training and Education Faculty, Widya Gama Mahakam Samarinda University, 2020)
Character education is also a vehicle for the socialization of characters that should be possessed by a human child to make them the noble creatures on earth. Character education requires habituation. Behavior of learners can be developed through character analysis that is developed within core competencies such as the character of responsibility. The sense of responsibility also influences students' learning achievement, while the character of cooperation can be raised in learning activities in class through group activities. In collecting data and information needed in research, the authors use data collection techniques or interviews with interviews, observations, and documentation. The character education of responsibility and cooperation in the 2013 curriculum thematic learning has been carried out in SD Negeri 2 Berkoh. In SD Negri 2 Berkoh Character of responsibility can be applied through doing homework, learning in class, doing assignments from the teacher while the character of cooperation can be applied through group work, playing in class, respecting the opinions of others. The implementation of responsibility character education and cooperation in the 2013 thematic learning at SD Negeri 2 Berkoh can be done through various activities such as learning activities, guidance, spontaneous activities, exemplary and habituation.